The spatial dose rate and energy characterization of a P 385 D-D Neutron Generator using a nested neutron spectrometer and a tissue equivalent proportional counter. (February 2017) - Orchard, G.M.; Hatakeyama, T.; Waker, A.J.
Abstract: A nested neutron spectrometer (NNS) and a tissue equivalent proportional counter (TEPC) were used to measure the spatial dose equivalent and energy neutron fluence distribution of a P 385 D-D Thermo Fisher Scientific Neutron Generator located in the mixed field dosimetry facility at the University of Ontario Institute of Technology. The P 385 Neutron Generator uses the D-D nuclear reaction to generate neutrons with an expected average energy of 2.5 MeV. The NNS uses a He-3 proportional counter to measure the neutron capture count rate as a function of nested cylindrical moderator thickness. Using the NNS and associated unfolding software, the energy neutron fluence distribution at various locations from the P 385 neutron generator were determined along with other radiation protection quantities of interest. Measurements of the dose equivalent rate were also conducted at the same locations using a 5-inch spherical TEPC and compared to the NNS results. The TEPC was further used to measure the dose equivalent as a function of radial distance from the neutron generator target and also for different P 385 operating conditions. Highlights: The characterization of a D-D neutron generator is presented. Novel nested neutron spectrometer was used. Complementary TEPC measurements were conducted. The spatial variation of neutron fluence is mapped.